Inferring flight parameters of Mesozoic avians through multivariate analyses of forelimb elements in their living relatives - Serrano Alarcón, Francisco José; Palmqvist-Barrena, Carlos Paul; Chiappe, Luis M.; Sanz, José L. (Cambridge University Press, 2017)
Our knowledge of the diversity, ecology, and phylogeny of Mesozoic birds has increased significantly during recent decades, yet our understanding of their flight competence remains poor. Wing loading (WL) and aspect ratio (AR) are two aerodynamically relevant parameters, as they relate to energy costs of aerial locomotion and flight maneuverability. They can be calculated in living birds (i.e., Neornithes) from body mass (BM), wingspan (B), and lift surface (S L). However, the estimates for extinct birds can be subject to biases from statistical issues, phylogeny, locomotor adaptations, and diagenetic compaction. Here we develop a sequential approach for generating reliable multivariate models that allow estimation of measurements necessary to determine WL and AR in the main clades of non-neornithine Mesozoic birds. The strength of our predictions is supported by the use of those variables that show similar scaling patterns in modern and stem taxa (i.e., non-neornithine birds) and the similarity of our predictions with measurements obtained from fossils preserving wing outlines. In addition, although our WL and AR values are based on estimates (BM, B, and S L) that have an associated error, there is no cumulative error in their calculation, and both parameters show low prediction errors. Therefore, we present the first taxonomically broad, error-calibrated estimation of these two important aerodynamic parameters in non-neornithine birds. Such estimates show that the WL and AR of the non-neornithine birds here analyzed fall within the range of variation of modern birds (i.e., Neornithes). Our results indicate that most modern flight modes (e.g., continuous flapping, flap and gliding, flap and bounding, thermal soaring) were possible for the wide range of non-neornithine avian taxa; we found no evidence for the presence of dynamic soaring among these early birds.
Keywords: Aves extinguidas; Aves - Vuelo; Adaptation; Body mass; Bird locomotion; Multivariate analysis